Conflicting genomic signals affect phylogenetic inference in four species of North American pines - Koralewski, Tomasz E.; Mateos, Mariana; Krutovsky, Konstantin V. (AoB plants, 2016)
Eleven nuclear genes and multiple phylogenetic techniques were used to study relationships among four of North American pines from subsection Australes (genus Pinus). Support for phylogenies reconstructed based on all data was generally weak and inconsistent among methods. Subsequent analysis revealed that certain topologies were supported by genes with common putative functionalities. Therefore, each set of genes was analysed independently. Recovered alternative topologies were highly supported and the results were consistent among methods. Multiple evolutionary hypotheses could potentially explain the observed patterns, although incomplete lineage sorting seems to be the simplest one. Adaptive evolutionary processes in plants may be accompanied by episodes of introgression, parallel evolution and incomplete lineage sorting that pose challenges in untangling species evolutionary history. Genus Pinus (pines) is one of the most abundant and most studied groups among gymnosperms, and a good example of a lineage where these phenomena have been observed. Pines are among the most ecologically and economically important plant species. Some, such as the pines of the southeastern USA (southern pines in subsection Australes), are subjects of intensive breeding programmes. Despite numerous published studies, the evolutionary history of Australes remains ambiguous and often controversial. We studied the phylogeny of four major southern pine species: shortleaf (Pinus echinata), slash (P. elliottii), longleaf (P. palustris) and loblolly (P. taeda), using sequences from 11 nuclear loci and maximum likelihood and Bayesian methods. Our analysis encountered resolution difficulties similar to earlier published studies. Although incomplete lineage sorting and introgression are two phenomena presumptively underlying our results, the phylogenetic inferences seem to be also influenced by the genes examined, with certain topologies supported by sets of genes sharing common putative functionalities. For example, genes involved in wood formation supported the clade echinata–taeda, genes linked to plant defence supported the clade echinata–elliottii and genes linked to water management properties supported the clade echinata–palustris. The support for these clades was very high and consistent across methods. We discuss the potential factors that could underlie these observations, including incomplete lineage sorting, hybridization and parallel or adaptive evolution. Our results likely reflect the relatively short evolutionary history of the subsection that is thought to have begun during the middle Miocene and has been influenced by climate fluctuations.